Understanding of Abdominal Compartment Syndrome among Pediatric Healthcare Providers. (29th July 2010) - Ejike, J. Chiaka; Newcombe, Jennifer; Baerg, Joanne; Bahjri, Khaled; Mathur, Mudit
Abstract : Background . The sparse reporting of abdominal compartment syndrome (ACS) in the pediatric literature may reflect inadequate awareness and recognition among pediatric healthcare providers (HCP). Purpose . To assess awareness of ACS, knowledge of the definition and intraabdominal pressure (IAP) measurement techniques used among pediatric HCP. Method . A written survey distributed at two pediatric critical care conferences. Results . Forty-seven percent of 1107 questionnaires were completed. Participants included pediatric intensivists, pediatric nurses, and others. Seventy-seven percent (n = 513 ) of participants had heard of ACS. Only 46.8% defined ACS correctly. The threshold IAP value used to define ACS was variable among participants. About one-quarter of participants (83/343), had never measured IAP. Conclusion . Twenty-three percent of HCP surveyed were unaware of ACS. Criteria used to define ACS were variable. Focused education on recognition of ACS and measuring IAP should be promoted among pediatric HCP.